ANALISIS PENERAPAN PERNYATAAN STANDAR AKUNTANSI KEUANGAN ( PSAK ) NO.1 TENTANG PENYAJIAN LAPORAN KEUANGAN PUSKESMAS KALIJAGA PERMAI - Suwandi; Yenni Rohmatun; Noviany (LPPM Sekolah Tinggi Ilmu Ekonomi Cirebon, 2021)
This research is a qualitative descriptive study conducted at the Kalijaga Permai Health Center. This study aims to find out how the implementation of PSAK No. 1 concerning the Presentation of Financial Statements at Kalijaga Permai Health Center (Balance Sheet, Operational Report, Cash Flow Statement, Notes to Financial Statements). The data collection method used is documentation. Based on the results of the study, it can be concluded that the Kalijaga Permai Health Center has implemented PSAK No. 1 in the Presentation of Financial Statements in the form of a Balance Sheet, Operational Report, Cash Flow Statement, and Notes to Financial Statements although there are some differences in the presentation of the Financial Statements of the Kalijaga Pemai Health Center with PSAK No. 1, namely the absence of a Change in Equity Report because all equity in the Kalijaga Permai Health Center belongs to the local government. There is a difference in the name of the Comprehensive Income Statement to the Operational Report, although there is a difference in name but the information presented in the Operational Report in general already presents information on income, costs, and the total surplus or deficit of the Kalijaga Permai Health Center, with the following details: Presentation of the Balance Sheet, Operational Report , Cash Flow Statements and Notes to Financial Statements have been able to present information in accordance with PSAK No.1.